The English language needs of Armed Forces officers - Surjeet Singh Jeggy (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2011)
The Malaysian Armed Forces (MAF), comprising the Army, the Navy and the Air Force, and entrusted with the important responsibility of national security, is also expected to project a positive image of Malaysia in the international arena as it (the MAF) engages in peace-keeping and relief operations with joint forces from various other countries. Like almost every other institution in the world, it has been impacted by globalisation, and is thus constantly engaging in efforts to upgrade itself in all aspects, especially those related to equipping itself with the necessary knowledge and expertise required to meet the demand for better services to the country and the people. Its efforts to increase efficiency and efficacy are built on the twin concepts of Revolution in Military Affairs (RMA) and the K-Force, and realised through the concept of the MAF as a learning organisation. The RMA aims to improve military effectiveness, while the K-Force attempts to produce a knowledge-enabled Armed Force, where its soldiers and officers have relevant knowledge and ICT skills, and are receptive to technological and global changes. A crucial issue here is that in order to fully utilise the potential of the RMA and the needs of a learning organisation, it is necessary to be proficient in the English language, as most of the military literature and technical manuals are in this language, as is all interaction with international joint forces. In addition, there is a need to enhance the proficiency of MAF personnel, especially the officers, as many of the daily activities of the MAF involve the use of the language; it is also the medium of instruction in the military colleges where MAF personnel are sent for courses. Despite the importance of the language, MAF personnel do not appear to have the necessary proficiency in the language to cope with their needs. It is thus the purpose of this study to look into the English language needs of the Armed Forces officers. The study also looks at the status quo of the English language in relation to the three Services (Army, Navy and Air Force), and the role played by the English language in the career development of an Armed Forces officer. Lastly, the study offers recommendations to the type of English language course needed to cater for the needs of Armed Forces officers in order to face a globalised and technological savvy world. The sample for this study comprises 138 officers from all three services undergoing training courses in two military institutions, namely, the Malaysian Armed Forces Defence College (MAFDC) and the Malaysian Armed Forces Staff College (MAFSC), which work with University Kebangsaan Malaysia and University Malaya, respectively, to offer courses to MAF personnel. The medium of instruction throughout the one-year course at these colleges is English. A mixed methods approach has been adopted for the study, and data was gathered via four investigative tools. The first is a questionnaire administered to the students of Course 35/2006 at the Staff College and for Course 26/2006 at the Defence College to cover the language needs of the students. Next, interviews were conducted with student leaders, the Directing Staff of the colleges, and the lecturers of the two universities. A document study was done to give further information on the usage of English, the curriculum and the appraisal system at both the Colleges. The findings show that all four language skills, namely, listening, speaking, reading and writing are important to the MAF officers. The findings also highlight the need for the Army to conduct at least 75% of their Junior Officers Career Courses in English in order to stem the decline in the command of the English language among Junior Officers, and to be at par with those at the Navy and the Air Force